2002
DOI: 10.1159/000049152
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical Vascular Dementia

Abstract: Vascular dementia (VaD) incorporates different vascular mechanisms and changes in the brain, and has different causes and clinical manifestations. Current criteria for VaD select an aetiologically and clinically heterogeneous group and this definitional heterogeneity has affected clinical trial results. Focus on a more homogeneous group, such as that with subcortical (ischaemic) VaD, could be an alternative in clinical drug trials. This subtype incorporates two small vessel clinical entities – ‘Binswanger’s di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 17 publications
2
66
0
3
Order By: Relevance
“…During long-term treatment, attention improves, probably because of adaptation of the cerebral circulation to lower BP, and this accounts for improvement also of executive functions, in spite of the similar BP control and greater cerebrovascular damage. Our data confirm the presence of mild cognitive impairment in hypertensive subjects, involving mainly executive functions, 26,27 and the protective effect of antihypertensive treatment against cerebrovascular damage. 9 Association of IMT to cognitive dysfunction has already been shown in patients with cerebrovascular disease and dementia.…”
Section: Discussionsupporting
confidence: 84%
“…During long-term treatment, attention improves, probably because of adaptation of the cerebral circulation to lower BP, and this accounts for improvement also of executive functions, in spite of the similar BP control and greater cerebrovascular damage. Our data confirm the presence of mild cognitive impairment in hypertensive subjects, involving mainly executive functions, 26,27 and the protective effect of antihypertensive treatment against cerebrovascular damage. 9 Association of IMT to cognitive dysfunction has already been shown in patients with cerebrovascular disease and dementia.…”
Section: Discussionsupporting
confidence: 84%
“…16 Because the onset of cerebral SVD is often insidious, clinically heterogeneous, and typically with mild symptoms, it has been suggested that the selection of subjects with cerebral SVD in clinical studies should be based on the more consistent brain imaging features. 17 Inclusion criteria were age between 50 and 85 years and cerebral SVD on neuroimaging (WML and/or lacunar infarct). Subsequently, the aforementioned acute or subacute clinical symptoms of SVD were assessed by standardized structured assessments (a questionnaire for TIA and stroke; 18 the Cognitive Failures Questionnaire, which also includes executive functions, for cognition; 19 the Falls Questionnaire 20 and the Freezing of Gait Questionnaire for gait; 21 and the Center of Epidemiological Studies-Depression scale 22 and use of antidepressive medication for depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…As suggested for clinical studies, patients were primarily selected on brain imaging features, because clinical symptoms of SVD are more heterogeneous and typically mild at the onset of cerebral SVD. 16 Therefore, inclusion criteria were (1) age between 50 and 85 years; and (2) WMLs and/or lacunar infarct(s) on neuroimaging. Subsequently, acute (transient ischemic attack or lacunar syndrome) or subacute (cognitive, motor or depressive) symptoms of SVD were assessed by standardized structured assessments.…”
Section: Study Populationmentioning
confidence: 99%